Evaluation of Serum Osteocalcin Level in Iraqi Postmenopausal Women with Primary Osteoporosis - Hamdi, Rana A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Osteoporosis (OP) is a chronic and a progressive disease characterized by low bone mass and micro-architectural deterioration of bone tissue, resulting in an increased risk of fracture. Osteocalcin is a non-collagenous protein synthesized and secreted by osteoblasts. Its main physiological functions are calcium ion homeostasis, maintain the normal bone mineralization rate, inhibit the abnormal formation of hydroxyapatite crystal, and to be involved in bone remodeling through a negative feedback mechanism.Objective: This study was planned to evaluate serum level of bone formation marker osteocalcin (OC) in postmenopausal women with and without primary osteoporosis; and study the correlation between serum osteocalcin level with women’s age.Subjects and Methods: Forty four (44) postmenopausal women were included in this study with age range (51-68 years). Subjects were divided into two groups: group A: twenty three (23) women with primary osteoporosis and group B: twenty one (21) women without primary osteoporosis (serve as controls). Patients were diagnosed as osteoporosis and controls as normal by measuring bone mineral density (BMD), using dual energy x-ray absorptiometry (DXA). In addition, serum calcium, phosphorous and alkaline phosphatase measured by spectrophotometer, while serum osteocalcin measured by enzyme linked immuno sorbent assay (ELISA).Results: Mean serum osteocalcin level in postmenopausal women with primary osteoporosis was significantly higher than controls (P